Protective Effect of Ginkgolic Acid in Attenuating LDL Induced Inflammation Human Peripheral Blood Mononuclear Cells via Altering the NF-κB Signaling Pathway - Zhang, Juan; Yan, Jifeng (Frontiers in Pharmacology, 2019)
Oxidized low-density lipoprotein (ox-LDL) is considered as the significant maker of inflammatory reaction and inflammation induced by ox-LDL was reported to play a crucial role in the pathogenesis of atherosclerosis. In the current study, we scrutinize the suppressive effect of ginkgolic acid against ox-LDL induced an oxidative and inflammatory response in human microvascular endothelial cells (HMEC-1) and human peripheral blood mononuclear cells (nPBMCs) and explores the mechanism of action. HMEC-1 cells treated with ox-LDL in the presence of different concentration of ginkgolic acid. MTT assay was performed for the estimation of cell viability effect. Reactive oxygen species (ROS), inflammatory cytokines and NF-kB activity also estimated.For the hPBMCs assay, the cells were isolated from the healthy volunteers and cultured. The cells were further divided into different group and received the ginkgolic acid. Additionally, ROS, inflammatory marker such as PGE2, LOX, NO, COX, protein expression and mRNA expression of TNF-α, IL-6 and VCAM-1 were estimated in the ox-LDL treated group. The result exhibited that ginkgolic acid treatment induced the cell viability boosting in ox-LDL treatment and intracellular ROS significantly decreased by ginkgolic acid. Pro-inflammatory cytokines also down-regulated by ginkgolic acid. Moreover, ginkgolic acid reduced the ox-LDL induced NF-kB. The mRNA and protein expression of TNF-α, IL-6 and VCAM-1 considerably increased in the ox-LDL treated group and ginkgolic acid significantly reduced the mRNA and protein expression. An inflammatory marker such as PGE2, LOX and NO were increased in the ox-LDL treated group and ginkgolic acid treated group exhibited the reduction of an inflammatory marker. On the basis of the result, we can conclude that ginkgolic acid significantly reduced and reverse the ox-LDL induced modulation and suggesting its anti-inflammatory effect via NF-kB pathway.